Bibliographie der paläarktischen Ichneumoniden. - Sachtleben, Hans (Contributions to Entomology = Beiträge zur Entomologie, 1962)
The publication contains a bibliography of papers on the Ichneumon-flies of the palearctic region, arranged in alphabetical order after the authors’ names, biographies of the deceased specialists of Ichneumonidae, a detailed index, additions and corrections.